TRANSLATION AND CROSS-CULTURAL ADAPTATION OF THE SHORT SEXUAL WELL-BEING SCALE SSWBS INTO VIETNAMESE - Huân, Nguyễn Thanh; Vĩ, Lâm Thành; Nhi, Trần Nguyên Thảo; Vân, Ngô Long; Hoàng, Nguyễn Lê Huy; Nguyên, Huỳnh Khôi; Duyên, Nguyễn Hoàng Mai; Bình, Phạm Hòa (Journal of Health and Aging, 2025)
According to the World Health Organization, sexual health constitutes an essential component of overall health. Nevertheless, culturally adapted instruments for assessing sexual health in Vietnamese remain scarce. Therefore, the development of an additional tool that is concise, user-friendly, and applicable in Vietnamese is warranted. This study aimed to translate and culturally adapt the Short Sexual Well-Being Scale (SSWBS) into Vietnamese. The translation process adhered to international guidelines and involved five steps. Two independent translators performed forward translation, followed by synthesis. The back-translated version demonstrated high equivalence with the original questionnaire, with all discrepancies being synonymous. During pilot testing with 40 healthcare professionals, 34 (85%) reported that the questionnaire was clear, comprehensible, and free of ambiguity, while six (15%) raised concerns regarding the wording of item 5. After further semantic clarification, these participants also confirmed the questionnaire’s clarity and comprehensibility. Overall, the translation and cultural adaptation of the SSWBS were conducted using a standardized methodology and were evaluated as simple, clear, and easy to understand.
Keywords: SSWBS; sexual satisfaction; sexual well-being